Memaknai Puasa Ramadhan Pada Siswa Sekolah Dasar Negeri 2 Bantarsoka Purwokerto - Wiyono, Teguh; Khalidy, Shodiq; Albab, Ulil (Jurnal Pengabdian Masyarakat (ABDIRA), 2024)
Fasting is a part of the pillars of Islam, and its practice can feel burdensome as it requires controlling desires and abstaining from eating and drinking from dawn until sunset. Even adults sometimes find fasting difficult, let alone young children, such as elementary school students. Therefore, there is a need to strengthen the understanding of the meaning of Ramadan fasting. One way to provide students with a deeper understanding is by involving them in studies or listening to lectures on the theme of understanding the meaning of Ramadan fasting, which will be held on Friday, April 5, 2024/25 Ramadan 1445 H at SD Negeri 2 Bantarsoka Purwokerto. The purpose of this community service activity is to enhance students' knowledge about the meaning of Ramadan fasting from an early age. The methods used are lectures and question-and-answer sessions. The outcome of this community service activity (PkM) is that students do not find fasting to be burdensome, as they understand it to be a religious obligation for every Muslim.